INFORMATION SECURITY OF KAZAKHSTAN MODERN REALES - G.A. Malik; Y.S. Ibadullayeva (Modern Scientific Technology, 2024)
This article is about the development of information security in Kazakhstan. It analyzes the conceФpt of information security of society, state, country, which fundamental acts, programs, documents exist, which cyber attacks prevail, and various incidents. The article also discusses the most important components of information security. In particular, the social, legal, financial, and economic security of Kazakhstan are disclosed.